Compassion-Oriented Mindfulness-Based Program and Health Professionals: A Single-Centered Pilot Study on Burnout - Marconi, Anna; Bàlzola, Maria Antonietta; Gatto, Ramona; Soresini, Annalisa; Mabilia, Diana; Poletti, Stefano (European Journal of Mental Health, 2019)
This pre-post, single-centered study evaluates the effects of a compassion-oriented mindfulness-based intervention on health professionals’ quality of life. The intervention was conducted in an Italian general hospital in the province of Milan. Between 2014 and 2015, thirty-four health professionals operating in the territorial psychiatric services followed an 18-week Compassion-Oriented Mindfulness-based Program. The program involved the practice of mindfulness meditation combined with a psycho-educational training. This pilot study analysed the impact of the intervention on mood, quality of life, and burnout-related characteristics. Outcome measures included the State-Trait Anxiety Inventory, the Beck Depression Inventory, the Maslach Burnout Inventory, the Five Facets of Mindfulness Questionnaire, and the Professional Quality of Life Scale. After the intervention, participants showed significantly decreased levels of depression, state anxiety, and emotional exhaustion. We found that an overall beneficial effect of the Compassion-Oriented Mindfulness-based Program existed in preventing burnout symptomatology. Non-evaluative and mindful attention was shown to improve stress resilience and coping strategies while simultaneously reducing worry and rumination. These results suggest that a compassion-oriented mindfulness program could prevent the development of anxiety and depression traits.